DARI JIAOZI KE PANGSIT: AKULTURASI DAN PENYEBARAN PANGSIT DI NUSANTARA - Syalwa Kasih Lasty Wibisono; Fadila Putri Cahyani; Nhayla Ramadhania; Zakiyya Wardah (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study examines the journey of dumplings (jiaozi) as a Chinese culinary dish that has undergone a process of acculturation since its introduction to Indonesia. Initially, dumplings were a traditional Chinese food with symbolic meaning as a symbol of good luck and prosperity. In their development in Indonesia, dumplings have undergone adaptations in ingredients, taste, and presentation in accordance with local preferences. This study uses a qualitative approach through literature review to trace the history, transformation, and localisation process of dumplings in Indonesian culinary practices. The results of the study show that dumplings are not only accepted as a complement to popular dishes such as chicken noodles and meatballs, but have also developed through various menu innovations. These findings confirm the contribution of the study that dumplings serve as a bridge for cultural acculturation, representing the meeting of Chinese and Indonesian culinary traditions and demonstrating the dynamics of cuisine as a space for cultural interaction that continues to evolve.